PfCSP-ferritin nanoparticle malaria vaccine antigen formulated with aluminum-salt and CpG 1018® adjuvants: Preformulation characterization, antigen-adjuvant interactions, and mouse immunogenicity studies - John M. Hickey; Nitya Sharma; Max Fairlamb; Jennifer Doering; Yetunde Adewunmi; Katherine Prieto; Giulia Costa; Benjamin Wizel; Elena A. Levashina; Nicholas J. Mantis; Jean-Philippe Julien; Sangeeta B. Joshi; et al. (Human Vaccines & Immunotherapeutics)
Circumsporozite protein (CSP), the most abundant surface protein in parasitic Plasmodium falciparum (Pf) sporozoite and an attractive target for malaria vaccine design, has been shown to induce protective humoral response in humans. In this work, we characterized and formulated a promising recombinant PfCSP immunogen (155) candidate consisting of two PfCSP epitopes (i.e. junction, NANP repeat) fused to H. pylori apoferritin forming a 24-mer nanoparticle. In addition, two N-linked glycans were engineered to mitigate possible anti-apoferritin immune responses, and a universal T-cell epitope was included to further enhance immunogenicity. Physicochemical characterization of the 155 antigen was performed including primary structure, post-translational modifications, conformational stability, and particle size. A competitive ELISA was developed to assess antigen binding to a PfCSP-specific mAb. The in vitro antigenicity of the 155 antigen was measured upon formulation with adjuvants, including aluminum-salts (i.e. AlhydrogelTM, Adju-PhosTM) and the TLR-9 agonist CpG 1018®, when freshly combined and after storage at different temperatures over 3 months. The in vivo immunological impact of various adjuvanted formulations of the 155 antigen was investigated in mice. The results support the formulation of 155 with AlhydrogelTM + CpG 1018® adjuvants as a promising recombinant malaria vaccine candidate from both a pharmaceutical and immunological perspective.